Electrocatalytic activity of Chemisorbed Hydroxyl ion towards Oxidation of Hydrogen peroxide anion in Alkaline media (Journal of Bangladesh Academy of Sciences, 2017)
In situ chemisorbed hydroxyl ion (OH-) onto clean polycrystalline gold (Au (poly)) electrode showed an extraordinary enhanced electrocatalytic activity towards oxidation of hydrogen peroxide anion (HO2-) in alkaline media. The oxidation of HO2- at the fabricated electrode was found to be a diffusion controlled process. The anodic transfer coefficient of the oxidation reaction was estimated as 0.47. Chloride ion (Cl-) replaced the chemisorbed OH- from the surface of the modified Au (poly) (OH-)Au (poly)) electrode leading to diminishing the observed electrocatalytic activity. The optimized concentration of KOH solution for the highest catalytic activity was found to be ca. 0.1 M. A linear calibration curve for various concentrations of HO2-? in the range of 0.5 to 5 mM was obtained having sensitivity equal to 1.028 A cm-2 M-1.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 29-36, 2017